The Benefits of Literature in Developing Talent and Self-Confidence for English Club Extracurricular Students in High School Level - Nabillah, Yumnaa Taqiyatul; Ittaqitafuzi, Ittaqitafuzi; Rohmana, Wahyu Indah Mala (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This study investigates the benefits of literature on the talent development and self-confidence of high school students participating in extracurricular English Club. Literature, derived from the Sanskrit word 'shastra', serves as a guide and source of information and includes various forms such as drama, poetry, tales, and speeches. Recognizing the importance of literature in developing talents and self-confidence, this study examines the role of extracurricular English Club in creating a supportive environment for students. Extracurricular activities, including English Club, play an important role in the character and academic development of young people. In response to the growing importance of English proficiency, some educational institutions have introduced English extracurricular programs to showcase students' potential and interests. This study, conducted at MAN 1 Kota Malang, East Java, used a descriptive qualitative approach to assess the impact of English clubs on students' literacy skills, self-confidence and talent development. The results showed that the English club at MAN 1 Kota Malang focuses on improving students' English skills, especially speaking. Through speaking, poetry, storytelling and drama exercises, students develop their imagination, analytical ability and general communication skills. Literature-oriented exercises help students overcome shyness, fear of making mistakes, and anxiety, and improve self-esteem. The study concludes that incorporating literature into extracurricular activities not only improves language skills, but also contributes to the development of talent and self-confidence, which are crucial for future success.